Teachers’ Strategies in Teaching Reading at the Eighth Grade Students of SMP Negeri 1 Palopo - Riska Pasa’pangan; Hafirah Patang; Rahmawati Upa (Universitas Cokroaminoto Palopo, 2023)
This descriptive qualitative study investigated the strategies used by English teachers in teaching reading to eighth-grade students at SMP Negeri 1 Palopo. Two teachers were selected through purposive sampling. Data were collected in July 2022 through classroom observation, semi-structured interviews, and documentation, then analyzed through data reduction, data display, and conclusion drawing. The findings revealed two dominant strategies. Teacher 1 applied Contextual Teaching and Learning by connecting texts with students’ daily experiences, using read-aloud and extensive-reading activities, and guiding students to identify unfamiliar vocabulary and important information. Teacher 2 used scaffolding by modelling fluent reading, guiding repetition, providing pictures and vocabulary support, and gradually transferring responsibility to students. Both teachers prepared lesson plans and materials and used motivational activities to maintain engagement. Limited vocabulary, low concentration, and the perception that English was difficult remained the main constraints. CTL and scaffolding functioned as complementary strategies for making reading texts meaningful and manageable for junior high school learners.